(untitled) (Castilla. Estudios de Literatura, 2021)
The purpose of this work is to make a comparative study of nature/countryside symbols in the works of Miguel Delibes and Mo Yan, two important literary figures in Spain and China. By analyzing the works of nature writing, including the construction of literary space, language and the function of nature/countryside, we will try to draw similarities between their literary creations and the differences in the sense of the nature/countryside towards them: for Delibes, it is the fate of mankind, while for Mo, it is the path to pursue his own essence.